Approaches in teaching foods and nutrition in the high school - Balinsat, Mary M.
The study analyzed the different approaches in teaching food and nutrition in high school with the hope that these will provide a more meaningful learning experience for the students and will bring about a better understanding and retention of the concepts learned.